Mediastinal Staging for Lung Cancer - Jacob Gelberg; Sean Grondin; Alain Tremblay (Canadian Respiratory Journal)
Staging of the mediastinal and hilar lymph nodes plays a crucial role in identifying the best treatment option for patients with confirmed or suspected lung cancer and, in many cases, can simultaneously confirm a diagnosis of cancer. Noninvasive modalities, such as computed tomography (CT), positron emission tomography (PET) and PET-CT, are an important first step in this assessment. Ultimately, invasive staging is frequently required to confirm or rule out the presence of metastatic disease within the lymph nodes. The present focused review describes and compares noninvasive and invasive modalities for mediastinal staging in lung cancer.